2014
DOI: 10.1115/1.4026011
|View full text |Cite
|
Sign up to set email alerts
|

Stagnation-Point Flow Toward a Stretching/Shrinking Sheet in a Nanofluid Containing Both Nanoparticles and Gyrotactic Microorganisms

Abstract: The stagnation-point flow and heat transfer toward a stretchingishrinking sheet in a nanofluid containing gyrotactic microorganisms with suction are investigated. Using a similarity transformation, the nonlinear system of partial differential equations is converted into nonlinear ordinary differential equations. These resulting equations are solved numerically using a shooting method. The skin friction coefficient, local Nusselt number, local Sherwood number, and the local density of the motile microorganisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…The author evaluated the effects of Prandtl number, Grashof number, bioconvection Rayleigh number, Schimdt number, Lewis number and bioconvection Péclet number on the concentration of motile micro-organisms. Zaimi et al [30] simulated energy transfer problem past a stretchable/shrinkable sheet placed in a nanofluid with gyrotactic microorganisms under suction. They observed that local Sherwood number, local Nusselt number, local density of the motile microorganisms and skin friction coefficient are enhanced with greater suction.…”
Section: Introductionmentioning
confidence: 99%
“…The author evaluated the effects of Prandtl number, Grashof number, bioconvection Rayleigh number, Schimdt number, Lewis number and bioconvection Péclet number on the concentration of motile micro-organisms. Zaimi et al [30] simulated energy transfer problem past a stretchable/shrinkable sheet placed in a nanofluid with gyrotactic microorganisms under suction. They observed that local Sherwood number, local Nusselt number, local density of the motile microorganisms and skin friction coefficient are enhanced with greater suction.…”
Section: Introductionmentioning
confidence: 99%
“…Basir et al [10] examined the enrobing hydrodynamics, heat and mass transfer in transient axisymmetric boundary layer flow of bioconvective nanofluids from an extending cylindrical body using Maple software. Zaimi et al [11] used a homotopy method to study the stagnation flow of nanofluids with bioconvection from a contracting or extending two-dimensional sheet. These studies all confirmed the marked influence of nano-particles on Nusselt and Sherwood numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Kuznetsov (2010) studied the bioconvection in a horizontal layer filled with micro-organisms suspended in a nanofluid using the Buongiorno model. Zaimi et al (2014a) showed that Brownian diffusion and thermophoresis are major factors for producing relative velocity between nanoparticles and the base fluid.The problem was solved using aGalerkin method to obtain the analytical solution for the critical Rayleigh number. The effect of gyrotactic microorganisms is to destabilize compared to nanofluid where the nanoparticles can either reduce or increase the value of the critical Rayleigh number depending on the nanoparticle distribution.…”
Section: Introductionmentioning
confidence: 99%